RANCANG BANGUN SISTEM INFORMASI PENJUALAN MENGGUNAKAN METODE WATERFALL - Anggi Oktaviani; Noer Hikmah (LPPM Universitas Bina Sarana Informatika, 2013)
Improvement or development of sales is the goal of any firms, both engaged in the sale ofgoods or services. Many things can be done so that sales can be increased, such as by a goodmarketing strategy. We need a media to publish information, whether information about thecompany or the goods will be sold. One of media that can be used is the internet. development ofthe Internet is fast and gives a significant influence in all aspects of our lives. Indonesia as one ofthe countries that have a population in many categories in the world, is a promising market ofInternet technology. companies can use the Internet as a tool to publish information or to makesales online, or called the E-Commerce. With the e-commerce or sales information can beaccessed wherever and whenever subscribers need. With this thesis the author makes the sale ofbaby equipment available on the web-based Store Babyness, using php and MySQL. With salesgrowth at stores Babyness proposed by the authors are expected to be easier to publish moreextensive sales and can be very helpful in trading activities effectively and efficientlyKeywords: Sale, Information, E-Commerce